Development of a novel completely‐in‐the‐canal direct‐drive hearing device. (22nd August 2016) - Djalilian, Hamid R.; Mahboubi, Hossein; Haidar, Yarah M.; Paulick, Peyton; Merlo, Mark W.; Bachman, Mark
Abstract : Objectives/Hypothesis: To develop a novel completely‐in‐the‐canal device capable of directly driving the tympanic membrane (TM) and ossicular chain from the ear canal. Study Design: Development and feasibility study. Methods: A voice coil actuator design was developed to drive the TM. Bench testing of the device using laser Doppler vibrometry (LDV) and sound recording was performed. Temporal bone studies using LDV were performed using different designs of the contact tip‐TM interface to find the most efficient method of sound transmission. Two short‐term clinical performance studies were performed using the latest 3‐mm‐wide device. Comparison was made to natural sound and to the Vibrant SoundBridge floating mass transducer simulator. Results: On bench testing, the device was found to have a low (<0.5%) total harmonic distortion in all frequencies above 400 Hz. Temporal bone studies revealed the device was capable of producing vibrations equivalent to 104 to 120 dB sound across most frequencies. The most efficient method of stimulation was when the device was coupled to the malleus. Short‐term clinical performance studies indicated that pure tones and complex sound can be presented with the device. The sound quality of the experimental device was rated as better than the SoundBridge simulator device. Conclusions: The direct‐drive hearing device is capable of producing a wide range of sound frequencies and amplitudes. The device can transmit complex sound with low power requirements. Further work on the development of the device is needed for long‐term and wider clinical use. Level of Evidence: NA Laryngoscope, 127:932–938, 2017